Incidence Rate and Risk Factors of Ectopic Pregnancy at Maternity Wards in Baghdad City’s Hospitals for the Year 2019 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Ectopic pregnancy is a condition of immense gynecological importance, particularly in thedeveloping world, because of the high morbidity and mortality associated with it and the enormous threatto life.Objectives:To assess the incidence rate and the risk factors of ectopic pregnancy at Maternity Wards inBaghdad City’s Hospitals for the year 2019.Methods:The study included a non-probability (convenient) sample consisted of (90)pregnant woman whohave ectopic pregnancies. The study subjects are recruited from 10 teachinghospitals in Baghdad,in theirfirsttrimester of gestation age. The studydata is collected from pregnant women’ edical records in the Departmentof Statistics, data are analyzed using descriptive and inferential data analysis process.Results: the results of the current study indicate that the incidence rate of ectopic pregnancy is (2.217)per1000 of population at risk for the year 2019. Smoking is accounted as the most predominant risk factorfor ectopic pregnancy (55.6%),Most of these pregnant women are between the ages of (15-24) years old(40.0%), college graduates (26.7%), government employees (52.2%), and have a monthly income (901.000-1.200.000) ID (32.2%).Conclusion:: Incidence rate of ectopic pregnancy at the maternity wards in Baghdad City’s hospitals is(2.217) per 1000 of population at risk for the year of 2019, The incidence rate of ectopic pregnancy has notbeen affected by the risk factors of infertility, previous ectopic pregnancies, IUCD, assisted reproductivetechniques and smoking of ectopic pregnancy and the incidence rate of ectopic pregnancy has not beenaffected by pregnant demographic characteristics of age, education, occupation and monthly income.